2022
DOI: 10.1136/pmj-2022-141749
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of gut-brain interaction in post-acute COVID-19 syndrome

Abstract: The novel coronavirus SARS-CoV-2 is responsible for the devastating pandemic which has caused more than 5 million deaths across the world until today. Apart from causing acute respiratory illness and multiorgan dysfunction, there can be long-term multiorgan sequalae after recovery, which is termed ‘long COVID-19’ or ‘post-acute COVID-19 syndrome’. Little is known about long-term gastrointestinal (GI) consequences, occurrence of post-infection functional gastrointestinal disorders and impact the virus may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…[19][20][21] Due to the well-established occurrence of post-infectious IBS, 22,23 many GI experts hypothesized that the COVID-19 pandemic could have predisposed to a rise of FGIDs with many COVID-19 infected patients eventually developing FGIDs. [24][25][26] This hypothesis has been supported by some recent adult studies. [27][28][29] In a multicenter investigation including 883 hospitalized COVID-19 adult patients, Marasco et al reported higher rates of IBS according to Rome IV criteria in the COVID-19 group (3.2%) versus the controls (0.5%; p = 0.045).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[19][20][21] Due to the well-established occurrence of post-infectious IBS, 22,23 many GI experts hypothesized that the COVID-19 pandemic could have predisposed to a rise of FGIDs with many COVID-19 infected patients eventually developing FGIDs. [24][25][26] This hypothesis has been supported by some recent adult studies. [27][28][29] In a multicenter investigation including 883 hospitalized COVID-19 adult patients, Marasco et al reported higher rates of IBS according to Rome IV criteria in the COVID-19 group (3.2%) versus the controls (0.5%; p = 0.045).…”
Section: Discussionsupporting
confidence: 63%
“…Interest in understanding the epidemiology of COVID‐19 infection in adults and children affected by gastrointestinal diseases has progressively grown during the pandemic 19–21 . Due to the well‐established occurrence of post‐infectious IBS, 22,23 many GI experts hypothesized that the COVID‐19 pandemic could have predisposed to a rise of FGIDs with many COVID‐19 infected patients eventually developing FGIDs 24–26 . This hypothesis has been supported by some recent adult studies 27–29 .…”
Section: Discussionmentioning
confidence: 92%
“…Freedberg DE et al 7 2022 Review Tian Y et al 8 2020 Review Ghoshal UC et al 9 2022 A case-controll study Benbari S et al 10 2022 Systematic Review and meta-analysis Zhang Y et al 11 2021 Systematic Review and Meta-analysis ReddWD et al 17 2020 Multicenter cohort study Leung TYM et al 18 2020 Meta-analysis Xiao F et al 19 2020 Comment Chen Y et al 20 2020 Cross sectional study Cheung KS et al 21 2020 Systematic Review and meta-analysis Nobel YR 22 2020 A case-control Study Schmulson M et al 23 2021 Review Blackett JW et al 24 2021 Retrospective controlled study Blackett JW et al 25 2021 Review Fernández-de-Las-Penas C et al 26 2021 Prospective control multinational study Qian Q et al 27 2021 Prospective control study Marasco G et al 28 2022 Prospective control multinational study Golla R et al 29 2022 Review disorders develop after some infections, and COVID-19 causes post-COVID-19 functional gastrointestinal disorders (9). According to Benvari et al, SARS-CoV-2 RNA could be detected through children's gastrointestinal specimens for more than 70 days after the loss of detectable RNA in the respiratory tract (10).…”
Section: Author Year Stylementioning
confidence: 99%
“…The GI involvement caused by Long COVID‐19 is related to both motility dysfunctions and gut‐brain interaction disorders (DGBI), classified by Rome IV, as a recent study by Nakhli et al highlights (Ebrahim Nakhli et al, 2022). Abdominal pain, nausea, and vomiting are extremely common in post‐COVID‐19 patients, but also alteration of the intestinal microbiome and increase in inflammatory cytokines (Golla et al, 2022). Microbiome alteration also seems to be a key point for the onset of the GI sequelae induced by SARS‐CoV‐2 infection.…”
Section: Introductionmentioning
confidence: 99%